Postscript on Mussel vs. Muscle in Relation to Bivalves - Ralph W. Dexter (Hello World!, 1976)
Confusion in the use of the common word 'mussel' or 'muscle' in reference to bivalve mollusks has been an issue of long standing. The problem has involved usage in publications and on maps, and especially with reference to what is officially recognized as the 'Muscle Shoals' in Tennessee. Writers especially concerned over this matter have been Ortmann (1924), Matthes (1925), Dexter (1961, 1967) and lsom (1971). Since my last report I have encountered a number of additional cases of sufficient interest to warrant publication.